Podejście Neuro-Edu-Techno (NET) w badaniach nad terapią pedagogiczną: Kazus ogniskowej dysplazji korowej - Przybyła, Tomasz; Klichowski , Michał (Studia Edukacyjne, 2019)
Focal cortical dysplasia (FCD) may vary in size and be located in any area of the human brain. In general, FCD causes epilepsy and it is usually associated with mental retardation. Even in case of epilepsy various types of treatment are identified, there is no complete educational therapy for developmental delays caused by FCD. Moreover, there are no works that synthetically discuss the possibilities of supporting such therapy by technology-based solutions. Method: Here, we investigate this issue using a systematic literature review. Results: Despite the fact that we were dealing with the lack of studies on technology-based educational therapy for students with cognitive problems due to FCD, we point out several potential benefits of this type of assistance. Discussion and conclusions: Our study clearly demonstrates that technology may strongly enhance educational therapy for developmental delays caused by focal cortical dysplasia and that there is a need for further neuro-edu-techno (NET) studies on this topic.